Impact of the COVID-19 pandemic on study experiences of Chinese students in Turin. A qualitative study - Huang, Lei (Antropologia Pubblica, 2024)
The worldwide pandemic caused by the outbreak of COVID-19 led to the enforced confinement of populations, in the hope that the official public health advice to distance socially could help to flatten the infection curve and to reduce the numbers of fatalities from the disease. The dramatic enforced changes in daily life due to the pandemic strongly affected the study experience of overseas students. By conducting semi-structured interviews with ten Chinese students in Turin, this paper examines how Chinese overseas students saw their study experience and future development before, during and after the COVID-19 crisis. The results reveal changes in the mentality of the Chinese students, as well as their social behaviour, parental relationships, and attitudes toward studying abroad and mobility. The context of the pandemic and the lockdown awakened students’ hidden personality traits, and their desire for Western credentials and transnational mobility competed with intensifying national sentiments and increased filial piety to parents. Finally, the paper highlights the tangible support to help international students manage their studies in Italy post-pandemic and points out future directions for research.